Quercetin as a Precursor for the Synthesis of Novel Nanoscale Cu (II) Complex as a Catalyst for Alcohol Oxidation with High Antibacterial Activity - Zahra Moodi; Ghodsieh Bagherzade; Janny Peters (Bioinorganic Chemistry and Applications)
Quercetin (3,3′,4′,5,7-pentahydroxyflavone) is one of the dietary flavonoids, distributed in medicinal plants, vegetables, and fruits. Quercetin has the ability to bind with several metal ions to increase its biological activities. In the last two decades, quercetin has attracted considerable attention due to the biological and pharmaceutical activities such as antioxidant, antibacterial, and anticancer. In the present study, quercetin and ethanolamine were used for the synthesis Schiff base complex, which was characterized by IR, 1H NMR, and 13C NMR spectroscopy. The Schiff base has been employed as a ligand for the synthesis of novel nanoscale Cu (II) complex. The product was characterized by FT-IR spectroscopy, FESEM, and XRD. Significantly, the product showed remarkable catalytic activity towards the oxidation of primary and secondary alcohols. The antibacterial activity of the final product was assessed against Staphylococcus aureus (Gram‐positive) and Escherichia coli (Gram‐negative) bacteria using an inhibition zone test. The synthesized nanoscale Cu (II) complex exhibited a strong antibacterial activity against both Gram-positive and Gram-negative bacteria.